Oxidative status of platelets in normal and thalassemic blood - Amer, Johnny; Fibach, Eitan (Thrombosis and Haemostasis, 2004)
Chronic platelet activation may be involved in thromboembolic complications, a leading cause of morbidity and mortality in β-thalassemia. Oxidative stress, with the generation of reactive oxygen species (ROS), is suspected to play a role in the pathophysiology of thalassemia and cardiovascular disorders. In the present study, we adapted flow cytometric techniques to measure oxidative state markers, ROS generation and reduced glutathione (GSH) content in platelets. Our results show that platelets obtained from β-thalassemic patients contain higher ROS and lower GSH levels than do platelets from normal donors, indicating a state of oxidative stress. In the absence of any known inherent abnormality in thalassemia platelets, this may be attributed to continuous exposure to oxidative insults from extra-platelet sources. We found that exposure of platelets to oxidants such as hydrogen peroxide and tertbutylhydroperoxide or to the platelet activators thrombin, calcium ionophore or phorbol myristate acetate stimulated the platelets’ oxidative stress.This was also increased by plasma of thalassemia patients, and decreased following treatment of the plasma with the iron-chelator Desferoxamin. Iron and hemin, the levels of which are augmented in plasma of thalassemia patients, stimulated the platelets’ oxidative stress.The oxidative status of the platelets was also affected by red blood cells (RBC); it was higher in normal platelets incubated with thalassemic RBC than with normal RBC. Normal RBC stimulated with hydrogen peroxide had a greater effect on platelets than did unstimulated RBC.The platelets’ oxidative stress was ameliorated by antioxidants such as N-acetyl-L-cysteine and vitamin C. Our findings indicate that in thalassemia, platelets undergo a state of oxidative stress, leading to their activation and potentially to thromboembolic consequences, and suggest that this hypercoagulable state might be treated with antioxidants.
Keywords: Thalassemia; platelets; free radicals; glutathione; flow cytometry